Optimization of Tube Hydroforming Process (without Axial Feed) by Using FEA Simulations. (2016) - Shinde, Rakesh A.; Patil, Bhushan T.; Joshi, Ketaki N.
Abstract: Tube hydroforming is the process of manufacturing light weight automotive components by applying fluid pressure. Success of Tube hydroforming process depends on best combination of material properties, process parameters, process sequence, and die geometry. Analysing the tube in square cross section die is simplest of hydroforming operation and the parameters effect can be further used for more complex hydroforming operation. In this work 3-D Finite Element model for the Tube Hydroforming (THF) developed using Creo Parametric 2.0, pre-processed using HyperMesh and solved using LS-DYNA explicit solver. This paper aims at identifying important parameters that affect the THF process without Axial feed. Taguchi's Design of Experiment technique is used to understand the effect of individual parameters as well as interaction of hydroforming process parameters such as die corner radius, length of tube, thickness of tube, internal pressure.